If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 = 5x + -2y Solving -10 = 5x + -2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -10 + -5x = 5x + -5x + -2y Combine like terms: 5x + -5x = 0 -10 + -5x = 0 + -2y -10 + -5x = -2y Add '10' to each side of the equation. -10 + 10 + -5x = 10 + -2y Combine like terms: -10 + 10 = 0 0 + -5x = 10 + -2y -5x = 10 + -2y Divide each side by '-5'. x = -2 + 0.4y Simplifying x = -2 + 0.4y
| 8(t-5)+4t=6(2t+3)-8 | | 6n-(4n+22)=5-(6n-2) | | 7x-5w+3x+6y+3y+2w= | | 28+19y=8+15y | | 10x-10y=16 | | 6x+15-2x=5.4+23 | | 8n+9=x | | S+5x=78 | | 45900/(1/2) | | 30600/(2/3) | | 16x^(-2/3)-4x^(1/3)/3 | | 4h+1=10+3h | | 16-f=-3 | | 3a+4=10+-1 | | (a+1)=2(a+2)-2 | | -20=4xm+8 | | 6x-17=2x+23 | | -20=4 | | 8-7a=-29 | | -2w-3w-26=39 | | 10x^9(x-3)+9x^10=0 | | 45x+60x+30x=180 | | 8-7a=-21 | | 2(x-4)-23=9-3x | | 35=17m-2m^2 | | -2(3+x)+5=-24 | | 30+4x=180 | | t=f+25v | | 1-12/(3z-3)=-20/(3z-3)^2 | | t=25v+f | | 12/(3z-3)=-20/(3z-3)^2 | | 5y+9=x-23 |